(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2025)
The findings of the archeological excavation of 2001 demonstrated that the Voltorre Monastery was built over two pre-existing churches which, as at today, are still unknown. Out of the two, the better preserved one, presents a Byzantine church floor plan dating back to Gothic Era. The contextualization of the Church in the Comum-Verbanus orographic narrow shines new lights on the toponym “Voltorre”. Just outside the current Romanic church, a monumental necropolis had been developing in three different phases. The most notable building, which is attributable to a clergyman, is beside the area where it is supposed to lay the sacramental pool, which was buried at the center of the presbytery of the now-demolished Goth Era church and whose whereabouts could have been still known at that time, or perhaps, was rediscovered in that circumstance.